2013
DOI: 10.4085/1062-6050-48.5.06
|View full text |Cite
|
Sign up to set email alerts
|

Sport and Team Differences on Baseline Measures of Sport-Related Concussion

Abstract: Context: With the advent of the National Collegiate Athletic Association's (NCAA's) mandating the presence and practice of concussion-management plans in collegiate athletic programs, institutions will consider potential approaches for concussion management, including both baseline and normative comparison approaches.Objective: To examine sport and team differences in baseline performance on a computer-based neurocognitive measure and 2 standard sideline measures of cognition and balance and to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…BESS summary scores, the sum of errors from the six stance and surface conditions were evaluated. One study of collegiate athletes found significant variation in BESS performance across sport,44 which was primarily driven by differences in athlete height. Two studies showed that participants performed worse (higher total errors) on the BESS at a live sporting event compared with a controlled locker room or clinical setting 45–47…”
Section: Resultsmentioning
confidence: 99%
“…BESS summary scores, the sum of errors from the six stance and surface conditions were evaluated. One study of collegiate athletes found significant variation in BESS performance across sport,44 which was primarily driven by differences in athlete height. Two studies showed that participants performed worse (higher total errors) on the BESS at a live sporting event compared with a controlled locker room or clinical setting 45–47…”
Section: Resultsmentioning
confidence: 99%
“…A large fraction of athletes were studied at baseline in an attempt to establish normative data. Two studies have been conducted to establish SCAT 45,46 normative data, 5 for the SCAT2, 13,19,47,50,58 but only 1 for the SCAT3. 16 These studies have reported on variations of the SCAT across ages, sex, and with concussion history.…”
Section: General Resultsmentioning
confidence: 99%
“…19,50,51,57,58 As a number of the early studies utilizing the SAC in an athlete population were conducted on exclusively male football teams, Despite these early reports, more recent studies with athletes have been inconsistent in demonstrating a relationship between sex and SAC scores. Zimmer et al, 58 in a study of SAC scores across various collegiate sport teams, reported no sex differences on the SAC. Yet, in a second study of college athletes by Zimmer et al, 57 females performed significantly better (27.63 vs 26.97; p = 0.004) than males.…”
Section: Effect Of Sexmentioning
confidence: 99%
“…Elbin et al [35] recently determined that athletes that self-reported ADHD, LD or combined ADHD/LD performed worse on a computerized neurocognitive measure and endorsed significantly more concussion-related symptoms at baseline as compared to those who denied ADHD, LD or ADHD/LD [35]. A recent study by Zimmer et al [14] also found that the sport played was associated with differential performance on both the CRI and on a standard test of balance, with sex and height playing important covariate roles. While the NFL, NBA and NHL currently only employ males within their leagues, the importance of understanding the differences in all levels of men's and women's baselines, as well as what differences persist at a post-concussion basis, cannot go overstated.…”
Section: The Rationale Behind Baseline Testingmentioning
confidence: 97%
“…Obviously, it is an improbability to eliminate all sources of statistical variance, whether it stems from group averaging or from individual sources. For example, a recent study of several hundred college athletes [14] found that the nature of the sport in which the player was involved is associated with significant performance differences in multiple baseline neurocognitive and balance measures. If post-trauma scores were compared only to group averages, such differences could easily result either in false positive identifications of concussion or, potentially more damaging, misses.…”
Section: The Rationale Behind Baseline Testingmentioning
confidence: 97%